Inculcating Islamic values contented in Qs. Luqman through english speaking materials - Muhammad Zuhri Anshari; Agus Widyantoro (Intelektual Pustaka Media Utama, 2020)
Islamic junior high schools have more duties than the public schools. They have the duty of teaching Islamic values to their students because these schools are established based on Islamic teachings. Islamic values must be included in all aspects of the school program. The materials used for teaching the students should also contain Islamic values. Unfortunately, based on the writers’ observation, not all Islamic junior high schools integrate Islamic values in the materials taught to the students. This fact challenges the English teachers in Islamic schools to select and to consider the appropriate values, cultures, and ideologies in teaching and learning English process. As a result, this paper is based on a study conducted to develop materials which integrate Islamic values for teaching Speaking in a private junior high school in Yogyakarta. The study was aimed to reveal the students’ needs in relation to the integration of the Islamic values in the materials for teaching the speaking skill and to know the appropriateness of the materials. This is an R and D study. To design the textbook the ADDIE Model was employed. To meet the textbook appropriateness, the designed textbook is analysed by conducting theoretical and empirical validation. The result of the study indicates that the designed materials are appropriate to be used in the Islamic schools.